Some Topological Properties Of Revised Fuzzy Cone Metric Spaces - A Muraliraj; R Thangathamizh (Ratio Mathematica, 2023)
In this paper, we introduced Revised fuzzy cone Metric space with its topological properties. Likewise A necessary and sufficient condition for a Revised fuzzy cone metric space to be precompact is given. We additionally show that each distinct Revised fuzzy cone metric space is second countable and that a subspace of a separable Revised fuzzy cone metric space is separable.